Carburization and wear behavior of self-lubricating Ti(C, N)-based cermets with various secondary carbides. Issue 19 (1st October 2021) - Wang, Zongyuan; Wan, Weicai; Wang, Jie; Fan, Kunyang; Li, Yuhe; Xiong, Ji; Du, Hao
Abstract: Self-lubricating Ti(C, N)-based cermets were manufactured using vacuum sintering and solid carburizing in this study, and the effects of various carbides on the carburization and wear behavior of the cermets were investigated. The findings demonstrate that solid carburizing resulted in strong graphite precipitation in all the Ti(C, N)-based matrices. Refractory carbides significantly affect the morphological characteristics of graphite in cermets. The activated carbon atoms in the cermet matrix are consumed in two ways: rearrangement followed by precipitation in the form of graphite and combination with metal atoms followed by precipitation in the form of carbides or carbonitrides. As the amount of refractory carbide dissolved in the binder phase increases, more carbon atoms are consumed by bonding with metal atoms, and less graphite is precipitated. The precipitation of carbides and carbonitrides in the ceramic phase increases the rim phase thickness. After carburization, the mechanical properties of the cermets were noticeably degraded owing to the introduction of graphite and the coarsening of ceramic particles. However, the presence of graphite significantly reduced the friction coefficient of the cermet material owing to its good lubrication effect. The decreased mass loss and better wear morphology suggest that the wear deterioration of all the cermets is remarkably mitigated by carburization. The wear properties of cermets are determined by the mechanical properties and the lubrication conditions of the contact surfaces, and good lubrication conditions can partially compensate for the degradation of the mechanical properties of cermets in the sliding wear process.